Direct and indirect effects of operant resources on co-creation experience: Empirical evidence from Airbnb consumers - Revi Hastari; Zehan Adela; Hanesman Alkhair; Alexander Joseph Ibnu Wibowo (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This study aims to empirically analyze the direct and indirect effects of operant resources on co-creation experience of Airbnb consumers. Specifically, this study examines operant resources' impact on perceived benefits, trust, and co-creation experience. In addition, this study also investigates the effect of perceived benefits, and trust on co-creation experience. We managed to collect a sample of 201 respondents obtained through online surveys. Respondents were consumers who have used Airbnb service offerings. Data were gathered using a questionnaire developed on the basis of a literature review. A convenience sampling was adopted in inviting consumers to participate in this study. The hypotheses were analyzed using simple and multiple linear regression analysis. The results show that operant resources are proven to influence perceived benefits, and trust of consumers. Likewise, perceived benefits, trust, and operant resources have been shown to influence the co-creation experience. The novelty and the most important contribution of this study are that it has succeeded in proving empirically the existence of the Service-Dominant Logic (S-D Logic) perspective.
Keywords: D83; L83; L86; M31; Z32; Z33; 650; service-dominant logic; operant resources; co-creation experience; value co-creation; tourism